Konsep Persahabatan Dalam Pemikiran Thomas Aquinas - Valentinus Saeng (Seri Filsafat Teologi, 2020)
Friendship is a word that is very familiar to us and we often hear it in the daily people’s conversation. The public or general opinion understands that friendship is the same as a companionship or a meaning of friend has an identical sense with a companion or a colleague. But how about this identification? Is it true? This paper attempts to elaborate the friendship meanings, by presenting its motives (intentions) and purpose (finality), so that we can understand the signification of friendship. The object of this research is the concept of friendship in Thomas Aquinas' thought. And the approach used in this research is a critical historical study.